BENZ WS: the Bologna ENZyme Web Server for four-level EC number annotation. Issue Volume 49:Issue W1(2021) (8th May 2021) - Baldazzi, Davide; Savojardo, Castrense; Martelli, Pier Luigi; Casadio, Rita
Abstract: The Bologna ENZyme Web Server (BENZ WS) annotates four-level Enzyme Commission numbers (EC numbers) as defined by the International Union of Biochemistry and Molecular Biology (IUBMB). BENZ WS filters a target sequence with a combined system of Hidden Markov Models, modelling protein sequences annotated with the same molecular function, and Pfams, carrying along conserved protein domains. BENZ returns, when successful, for any enzyme target sequence an associated four-level EC number. Our system can annotate both monofunctional and polyfunctional enzymes, and it can be a valuable resource for sequence functional annotation. Graphical Abstract: